Checking the Triple Product Rule for the Compression and Stretching of Materials - Stepanov, Igor A. (European Journal of Applied Sciences, 2025)
It is shown here that the well-known thermodynamic relation which stems from the triple product rule is not valid for descriptions of the compression and stretching of almost all materials.